Penerapan Quality Control Circle (QCC) dengan Siklus PDCA 8 Langkah untuk Perbaikan Proses Perakitan pada Produksi Drape - Septiana, Muhamad Fikri; ., Setiawan; Purwanto, Cipto (Jurnal Sains dan Teknologi (JSIT), 2026)
The quality standards in the assembly process of hoses and connectors for drape products at PT XYZ still face issues related to the high number of non-conforming products (NG), caused by difficulties in assembling the hose to the connector due to uneven and imprecise hose cutting results. This condition leads to increased customer complaints due to installation difficulties on the user's side. Additionally, the variation in hose cutting results causes inconsistencies in product quality, increasing the risk of production cost wastage. This study aims to identify the main causes of defects in the hose and connector assembly process and formulate a systematic improvement proposal to reduce NG levels and enhance the production process quality. The method used is Quality Control Circle (QCC) with an eight-step PDCA approach. Data collection techniques include direct observation in the production area, interviews with operators and related teams, and analysis of historical NG product documentation. Root cause analysis is carried out using the Seven Tools of Quality, particularly the Pareto chart and fishbone diagram, to determine the dominant factors causing the issue. The results show that the main cause of defects comes from the manual and imprecise hose cutting method, which complicates the connector assembly process. The proposed improvements, including the design and implementation of a hose cutting machine, the use of cutting jigs, and operator training, have proven effective in reducing NG levels and improving the consistency of the hose and connector assembly process quality.